GLOBALIZATION AND NATIONAL IDENTITY AWARENESS - Zafar Uzakovich Khayitov (Academia Science Repository, 2023)
Viewed in the broader time dimension of history, this is in fact, political upheavals unprecedented in history, which began at the beginning of the 20th century, algal-dives, excessive rapid scientific and technological advances, into nature the acceleration of the “attack " against bearish, as huge and wide as the demographic explosion was one of the components of the scale changes. To Individual imagination according to just a hundred years ago, many of these changes are natural and progressive calculated, complexity and negative aspects were not visible to many, even when it appears that in the eyes of the majority of mankind, this is their personal outside of his life, somewhere else, not dependent on them it seemed to happen due to objective laws.